NADH-fluorescence scattering correction for absolute concentration determination in a liquid tissue phantom using a novel multispectral magnetic-resonance-imaging-compatible needle probe - Braun, Frank; Kränzlin, Bettina; Gretz, Norbert (Measurement science and technology, 2017)
In this report, a quantitative nicotinamide adenine dinucleotide hydrate (NADH) fluorescence measurement algorithm in a liquid tissue phantom using a fiber-optic needle probe is presented. To determine the absolute concentrations of NADH in this phantom, the fluorescence emission spectra at 465 nm were corrected using diffuse reflectance spectroscopy between 600 nm and 940 nm. The patented autoclavable Nitinol needle probe enables the acquisition of multispectral backscattering measurements of ultraviolet, visible, near-infrared and fluorescence spectra. As a phantom, a suspension of calcium carbonate (Calcilit) and water with physiological NADH concentrations between 0 mmol l -1 and 2.0 mmol l -1 were used to mimic human tissue. The light scattering characteristics were adjusted to match the backscattering attributes of human skin by modifying the concentration of Calcilit. To correct the scattering effects caused by the matrices of the samples, an algorithm based on the backscattered remission spectrum was employed to compensate the influence of multiscattering on the optical pathway through the dispersed phase. The monitored backscattered visible light was used to correct the fluorescence spectra and thereby to determine the true NADH concentrations at unknown Calcilit concentrations. Despite the simplicity of the presented algorithm, the root-mean-square error of prediction (RMSEP) was 0.093 mmol l -1 .